The permeation of dynorphin A 1–6 across the blood brain barrier and its effect on bovine brain microvessel endothelial cell monolayer permeability - Sloan, Courtney D. Kuhnline (2012)
Dynorphin A 1–17 (Dyn A 1–17) is an endogenous neuropeptide known to act at the kappa opioid receptor; it has been implicated in a number of neurological disorders, including neuropathic pain, stress, depression, and Alzheimer’s and Parkinson’s diseases. The investigation of Dyn A 1–17 metabolism at the blood-brain barrier (BBB) is important since the metabolites exhibit unique biological functions compared to the parent compound. In this work, Dyn A 1–6 is identified as a metabolite of Dyn A 1–17 in the presence of bovine brain microvessel endhothelial cells (BBMECs), using LC-MS/MS. The transport of Dyn A 1–6 at the BBB was examined using this in vitro cell culture model of the BBB. Furthermore, the permeation of the BBB by the low molecular weight, permeability marker fluorescein was characterized in the presence and absences of Dyn A 1–6.